2014
DOI: 10.2991/ijndc.2014.2.3.3
|View full text |Cite
|
Sign up to set email alerts
|

Test Image Generation using Segmental Symbolic Evaluation

Abstract: Image processing applications have played a vital role in modern life and they are required to be well tested due to their significance and human dependence on them. Testing of image processing application is difficult due to complex nature of images in terms of their generation and evaluation. The presented technique is first of its type to generate test images based on symbolic evaluation of program under test. The idea is based on the fact that, neighboring image operations are applied by selecting a segmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…In rotation walking adjustment part, the relative acute angle between a robot and target is regarded as the input and the rotational speed is the output. Especially, the relative distance and acute angle can be obtained by some methods, such as image processing methods [30][31][32][33], localization techniques [34][35][36], mapping techniques [37][38], noise reducing method [39][40] and so on.…”
Section: Adaptive Fuzzy Parameters Adjustment Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In rotation walking adjustment part, the relative acute angle between a robot and target is regarded as the input and the rotational speed is the output. Especially, the relative distance and acute angle can be obtained by some methods, such as image processing methods [30][31][32][33], localization techniques [34][35][36], mapping techniques [37][38], noise reducing method [39][40] and so on.…”
Section: Adaptive Fuzzy Parameters Adjustment Methodsmentioning
confidence: 99%
“…according to (33) with the r ε being the range of maximal allowable fuzzy distance. After the fuzzy output vector } ,..., 2 ,…”
Section: Published By Atlantis Pressmentioning
confidence: 99%
“…In the article by (Hui & Huang, 2013), the authors say that random testing is considered unbiased and empirically it is shown that metamorphic testing shows better results with random tests in terms of mutation score and fault detection ratio. In the article by (Jameel & Lin, 2014), the authors say that test cases with higher code coverage are considered more effective in terms of their error detection capabilities. We have selected successful test cases randomly in our experimentation.…”
Section: Selection Of Test Casesmentioning
confidence: 99%